The Neonatal Neurobehavioral Effects of Mepivacaine for Epidural Anesthesia During Labor. Issue 3 (July 1986) - Abboud, Therese K.; Kern, Steven; Jacobs, Jerry; Murakawa, Kasushige; Sarkis, Faruk; Soraya, Manoutchehn
Abstract : The effects of epidural anesthesia on the early neonatal neurobehavioral scale (ENNS) following delivery were studied in 20 parturients given 1.5% mepivacaine epidural anesthesia during labor and delivery. These results were compared to those obtained in a control group of 16 neonates whose mothers received no analgesics, medications, or local anesthetics for labor or delivery. There was no significant difference in ENNS in the two groups of neonates. Mepivacaine, as administered in this study, has no adverse effects on the early neurobehavioral status of the neonate.